2020
DOI: 10.1016/j.envres.2019.108888
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the visibility of smokers across a large capital city

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…This sampling procedure has been used in previous studies. (23,24) The spatial distribution of these census tracts is shown in the supplementary material (figure S1).…”
Section: Study Area and Project Designmentioning
confidence: 99%
See 2 more Smart Citations
“…This sampling procedure has been used in previous studies. (23,24) The spatial distribution of these census tracts is shown in the supplementary material (figure S1).…”
Section: Study Area and Project Designmentioning
confidence: 99%
“…A similar procedure to define points for validation has been used in previous studies. (20,24) At each point-location, we conducted the same measurement procedure as in stage 2. To obtain these measures, we visited each point and collected data on the number of cigarette butts in a 1-meter radius (size of the pixel in the GIS analyses), and in a 3-and 5-meters radius for sensitivity analyses.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“… 9–11 A recent systematic assessment of studies assessing effectiveness of outdoor smoke-free policies identified the lack of research involving actual geographic mapping of smoking patterns and visibility of smokers in the area as a key knowledge gap. 12 A smoke-free outdoor policy has the potential to denormalize and discourage smoking, support smokers who want to quit, and to protect people from secondhand smoke. 13–16 …”
Section: Introductionmentioning
confidence: 99%
“…In the city of Barcelona, outside areas in bars and restaurants were the most common outdoor places for smokers to smoke following comprehensive legislation for all indoor public places ( Sureda et al, 2015 ). Moreover, hospitality venue surroundings in the city of Madrid were the outdoor areas with the highest visibility of smokers ( Valiente et al, 2020 ). Given that outdoor hospitality settings are usually on the street and visible for pedestrians, regulations restricting indoor smoking may have also enhanced the visibility of smoking ( Kennedy et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%